Ergonomic Improvement of Learning Environment - Poderienė, Giedrė (Acta Paedagogica Vilnensia, 2006)
Environment has to be taken care in such a way that it would be a source of human health and well-being (European Center of Environment, 1989). National reform of education and development of learning pays a considerable amount of attention to the building of modern environment and its improvement. However, in education literature and in pedagogical practice there is a lack of systemic review of the goals of the modern environment of education, structure and reference criteria, principles and conceptual reference for growth. There exist no standards for the creation and improvement of the school environment. Every institution develops its environment as it considers appropriate, depending on the conditions and opportunities. Often in this process the scientific principles, particularly ergonomic principles are neglected. Therefore it is important to follow the principles of healthy learning environment. Pedagogical ergonomics seeks to alter not people but the conditions in the learning environment. Different physical factors of the environment: composition of the air, meteorological situation (humidity, streams of air, temperature, atmospheric pressure, radiation), light, noise and vibration, human movement speed in the environment (acceleration and overload) have a big influence on the functional conditions of the learning process (health and disposition) and on the capacity to perform. The article analyses the approach to the design and development of the learning environment with the help of ergonomic means. It presents and analyses results of the experiment of the learners' workspace design.
Keywords: modern educational environment; classroom material environment; workplace; ergonomic parameters and tools